Experimental Investigation of Rejuvenated Asphalt Mixtures Using Bio-Oils from Different Biomass Sources - Furtana, Beyza; Yılmaz, Mehmet; Altundoğan, Hamdi Soner (My University, 2024)
Asphalt mixes containing Recycled Asphalt Pavement (RAP) materials are generally harder than traditional mixes. Different rejuvenators are used to soften recycled asphalt pavement by reducing this hardness. In this study, recycled asphalt pavement was added to bituminous hot mixtures at 3 different rates (25%, 50% and 75%). To rejuvenate bituminous hot mixtures containing RAP, three different rejuvenators (pine cone, olive pomace and wheat straw) were added to the mixtures. This study investigated the effect of asphalt mixtures containing RAP and rejuvenator on the mechanical properties. Marshall test and moisture damage test were performed to examine the mechanical properties of asphalt mixture samples. As the bio-oil content in asphalt mixtures increases, the stability values of the mixtures decrease. As the bio-oil ratio in asphalt mixtures increases, tensile strength (TS) values decrease in both unconditioned and conditioned mixtures. While the increase in bio-oil reduces the tensile strength ratio, the shrinkage ratio of mixtures prepared with RAP increases. The bio-oil derived from pomace has been identified as the most effective rejuvenator among those tested.
Keywords: Biomass; Pyrolysis; Bio-oil; RAP; Rejuvenator